Developing open source APIs for an information retrieval system. - Chen, Tun Lin. (2008)
This project focuses on an open source XML information retrieval software, eXist that provides the basic functionalities of indexing and querying of XML databases. The APIs developed index a batch of XML documents in a directory and automatically create the search user interface and result list page for that directory.